Two-stage CD8+ CAR T-cell differentiation in patients with large B-cell lymphoma - Guoshuai Cao; Yifei Hu; Tony Pan; Erting Tang; Nicholas Asby; Thomas Althaus; Jun Wan; Peter A. Riedell; Michael R. Bishop; Justin P. Kline; Jun Huang (Nature Communications)
Abstract Advancements in chimeric antigen receptor (CAR) T-cell therapy for treating diffuse large B-cell lymphoma (DLBCL) have been limited by an incomplete understanding of CAR T-cell differentiation in patients. Here, we show via single-cell, multi-modal, and longitudinal analyses, that CD8+ CAR T cells from DLBCL patients successfully treated with axicabtagene ciloleucel undergo two distinct waves of clonal expansion in vivo. The first wave is dominated by an exhausted-like effector memory phenotype during peak expansion (day 8–14). The second wave is dominated by a terminal effector phenotype during the post-peak persistence period (day 21–28). Importantly, the two waves have distinct ontogeny from the infusion product and are biologically uncoupled. Precursors of the first wave exhibit more effector-like signatures, whereas precursors of the second wave exhibit more stem-like signatures. We demonstrate that CAR T-cell expansion and persistence are mediated by clonally, phenotypically, and ontogenically distinct CAR T-cell populations that serve complementary clinical purposes.